Using the Generic Model of Psychotherapy to Develop a Culturally-Sensitive Approach to Psychotherapy With Sexual and Gender Minority Patients - Tomicic, Alemka; Martínez, Claudio; Rodríguez, Juliana (Frontiers in Psychology, 2020)
This article discusses how the Generic Model of Psychotherapy (Orlinsky & Howard, 1987) can help organize psychotherapy research and the knowledge in the field of psychotherapy for sexual and gender minority patients. The structure that this traditional model provides is a good foundation for research in this field, inasmuch as it stresses macrosocial aspects that determine the provision of psychotherapy and contextualize its outcomes. Each one of the main components offered by the Generic Model of Psychotherapy -Determinants, Processes and Consequences-, are specified for psychotherapy with LGBT patients and are illustrated with a selection of already existing research in the field of sexual minorities; they also stress areas marked by knowledge gaps that require future developments. In addition, a set of questions are proposed to contribute to new studies, including the clinical implications that can be derived from this model.